The membrane: transertion as an organizing principle in membrane heterogeneity - Matsumoto, Kouji; Hara, Hiroshi; Fishov, Itzhak; Mileykovskaya, Eugenia; Norris, Vic (Frontiers in Microbiology, 2015)
The bacterial membrane exhibits a significantly heterogeneous distribution of lipids and proteins. This heterogeneity results mainly from lipid-lipid, protein-protein and lipid-protein associations which are orchestrated by the coupled transcription, translation and insertion of nascent proteins into and through membrane (transertion). Transertion is central not only to the individual assembly and disassembly of large physically linked groups of macromolecules (alias hyperstructures) but also to the interactions between these hyperstructures. We review here these interactions in the context of the processes in Bacillus subtilis and Escherichia coli of nutrient sensing, membrane synthesis, cytoskeletal dynamics, DNA replication, chromosome segregation and cell division.